A Pd(ii)-catalyzed C–H activation approach to densely functionalized N-heteroaromatics related to neocryptolepine and their evaluation as potential inducers of apoptosis1. Issue 56 (19th June 2015) - Sunke, Rajnikanth; Kumar, Vimal; Ashfaq, Mohd Ashraf; Yellanki, Swapna; Medisetti, Raghavender; Kulkarni, Pushkar; Shivaji Ramarao, E. V. Venkat; Ehtesham, Nasreen Z.; Pal, Manojit
<x xml:space="preserve">Abstract</x> Bioactive indoloquinolines are synthesized via Pd(ii)-catalyzed intramolecular oxidative C–H alkenylation as the key step.